A Criminological Perspective on Suicide In The Jurisdiction of Police Resort, Polewali Mandar District - Fadli Yasser (Journal of Scientific Research, Education, and Technology (JSRET), 2022)
There were 3 cases of suicide in Polewali Mandar Regency throughout 2021 no one is criminally responsible for the suicide. Even though the act of suicide has a motive that causes someone to be compelled to commit suicide. So it is necessary to know what factors caused the act. Suicide in the jurisdiction of Polewali Mandar and What are the efforts of the Polewali Mandar District Police to suppress the increase in suicide cases in the jurisdiction of Polewali Mandar. Polewali Mandar. The results of the study describe the factors of suicide that occurred in the Polewlai Mandar area, namely, firstly, the use of drugs based on a case of hanging himself in the Tinambung market complex. To doubts about self-esteem, as well as giving rise to a feeling that they are not liked, not needed, not understood and not loved by the people around them. This factor occurs in several cases in Polewali mandar. The Polewali Mandar Resort Police did not optimize the task of Bhabinkamtibmas in carrying out their main duties to carry out activities that are directly related to the community in providing education to reduce the increase in suicide cases in Polewali Mandar. The Polewali Mandar police should, after carrying out an investigation and knowing the factors causing the suicide case, should use a series of these factors to make policies that regulate police activities in educating the public and students about problem solving without harming themselves. The Bhabinkamtibmas division to carry out its tupokis in accordance with the Chief of Police Regulation Number 3 of 2015.